Air Pollution Impairs Marathon Performance: A Cross-Sectional Analysis of 2.7 Million Finishers Across Six World Marathon Majors - James A. Donaldson; Samuel Cai; Josh Vande Hey; Anna L Hansell; Thomas Yates; G. Andre Ng; Jamie O’Driscoll (Sports Medicine - Open, 2026)
Abstract Background Ambient air pollution impairs respiratory and cardiovascular function during exercise, yet evidence on its effects across the full spectrum of endurance performance remains limited. Objectives To quantify the association between race-day ambient air pollution and marathon finishing time across six World Marathon Majors, and to determine whether effects vary by sex, age group, and performance level. Methods We analysed 2,756,553 net finishing times from six World Marathon Majors (Berlin, Boston, Chicago, London, New York City, and Tokyo) for editions held between 2010 and 2024. Race-day nitrogen dioxide (NO₂) and fine particulate matter (PM₂.₅) concentrations were obtained from the Copernicus Atmosphere Monitoring Service (CAMS) global reanalysis dataset. Linear mixed-effects models with random intercepts for each of 75 marathon–year events estimated pollution effects on finishing time, adjusting for heat index, wind speed, and temporal trends. Stratified analyses were conducted among 1,815,188 runners with available age data. Results Of the pollutants examined, NO₂ showed the stronger association with finishing time. Each 1 µg/m 3 increase was associated with 1.43 min slower finishing time in men (95% confidence interval [CI] 0.66 to 2.21) and 1.56 min in women (95% CI 0.63 to 2.48). PM₂.₅ effects were not statistically significant: −0.13 min per µg/m 3 in men (95% CI −0.67 to 0.40) and −0.14 min per µg/m 3 in women (95% CI −0.76 to 0.49). Recreational runners experienced NO₂ effects approximately six-fold larger than elite runners (2.12 vs 0.34 min per µg/m 3 ); expressed as a percentage of mean finishing time, this gradient persisted (0.67% vs 0.18%). Younger runners (18–29 years) showed larger effects than older runners (2.17 vs 1.32 min per µg/m 3 for ≥60 years). Kolmogorov–Smirnov tests confirmed that higher NO₂ was associated with rightward shifts across the entire finishing time distribution. Conclusions Ambient air pollution, particularly NO₂, is associated with impaired marathon performance in a dose-dependent manner, with the largest effects among recreational runners. These findings have implications for race management and public health policy regarding outdoor physical activity in urban environments.